Black speckled duodenal mucosa. Issue 2 (2nd April 2020) - Kudaravalli, Pujitha; Saleem, Sheikh A.; Riaz, Sana; Pendela, Venkata Satish; Vasigh, Mostafa; Heisig, David
Abstract: Pseudomelanosis duodeni is a rare incidental finding seen on endoscopy and has the characteristic appearance of flat, black-speckled pigmented mucosa. We present the case of an 83-year-old woman who presented with gastrointestinal bleeding and was found to have pseudomelanosis duodeni. The finding has no diagnostic or prognostic significance. Therapeutic chelation or endoscopic follow-up is not recommended.